Reirradiation of Whole Brain for Recurrent Brain Metastases: A Case Report of Lung Cancer With 12-Year Survival - Li, Minmin; Song, Yanbo; Li, Longhao; Qin, Jian; Deng, Hongbin; Zhang, Tao (Frontiers in Oncology, 2021)
The whole brain radiotherapy (WBRT) for brain metastases (BMs) was considered to be dose limited. Reirradiation of WBRT for recurrent BM has always been challenged. Here, we report a patient with multiple BMs of non-small-cell lung cancer (NSCLC), who received two courses of WBRT at the interval of 5 years with the cumulative administration dose for whole brain as 70Gy and a boost for local site as 30Gy. Further, after attacked by relapse in brain again, he got an extra γ-knife for local brain metastasis at the third time after 5 years. The overall survival was 12 years since he was diagnosed as NSCLC with multiple brain metastases at initial. Meanwhile, each time of radiotherapy brought good tumor response to brain metastasis. Outstandingly, during the whole survival, he had a well quality of life (QoL) with Karnofsky Performance Score (KPS) above 80. Even after the last γ-knife was executed, he had just a mild neurocognitive defects. In conclusion, with cautious evaluation of a patient, we suggest reirradiation of WBRT could be a choice and the cumulative radiation dose of brain may be individually modified.